2020
DOI: 10.1617/s11527-020-01570-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fibre type and content on performance of bio-based concrete containing heat-treated apricot shell

Abstract: The heat-treated apricot shell can be utilized as coarse aggregates for producing sustainable bio-based lightweight concrete with good compressive strength but poor tensile strength. In order to improve the tensile properties of apricot shell concrete (ASC), the effects of polypropylene (PP) fibre, glass (G) fibre and basalt (B) fibre at various volume fractions (Vf) (0.25%, 0.5% and 0.75%) on the performance of ASC were investigated. The results indicated that the fibre type had no significant effect on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
4
4
0
Order By: Relevance
“…Also, incorporation of banana fibres in concrete alters its failure mode from a brittle to plastic failure and hence mitigating the formation and propagation of cracks. Similar results were observed by other researchers who reported that fibres control microcrack formation and lead to the delay in failure and hence increasing the ultimate strength and strongly contribute in the load carrying capacity of the postpeak phase [58][59][60]. It has also been suggested that incorporating fibres in concrete enables it to resist extra compressive stress by blocking and redirecting the cracks [61].…”
Section: Test Methodsupporting
confidence: 87%
See 3 more Smart Citations
“…Also, incorporation of banana fibres in concrete alters its failure mode from a brittle to plastic failure and hence mitigating the formation and propagation of cracks. Similar results were observed by other researchers who reported that fibres control microcrack formation and lead to the delay in failure and hence increasing the ultimate strength and strongly contribute in the load carrying capacity of the postpeak phase [58][59][60]. It has also been suggested that incorporating fibres in concrete enables it to resist extra compressive stress by blocking and redirecting the cracks [61].…”
Section: Test Methodsupporting
confidence: 87%
“…A similar behavior of an initial increase in tensile strength up to a certain amount of fibre content and thereafter experiencing a drop with further increase in fibre content has been observed in another study [58]. Wu et al [58] observed that for all fibres used (i.e. polypropylene, glass, and basalt fibres), splitting tensile strength of apricot shell concrete (ASC) significantly increased when the fibre content was increased from 0.25 to 0.50% but then dropped when the fibre content was increased from 0.5 to 0.75%.…”
Section: Splitting Tensile Strength Splitting Tensile Strengths Of Plain Concrete (F T(plain)supporting
confidence: 85%
See 2 more Smart Citations
“…With excellent toughness, BF inhibits the formation of micro-cracks in the concrete and improves its compactness [ 34 ]. Many studies indicate that the use of BF enhances concrete’s resistance to sulfate attack [ 33 , 35 , 36 , 37 , 38 , 39 ]. Wang et al [ 38 ] found that an appropriate amount of BF can limit the expansion of pores and cracks, thereby enhancing corrosion resistance, but excessive BF would adversely affect durability.…”
Section: Introductionmentioning
confidence: 99%